Childhood Vaccination Decisions during the Pandemic: Tradition, Generational Influence, and Spiritual Perspectives - Fitriyah, Nurin Nadzifatil; Maulidina, Akmal (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2024)
Background: Vaccination is an attempt to form active immunity in an individual. Vaccination is carried out as a preventive measure against infection, both in adults and children. This study aims to determine the effect of parental attitudes, generational influenced, and spiritual contexts on children's vaccination decisions, in this case, the COVID-19 vaccination. Methods: This study used a cross-sectional online survey method, with parents who have children aged 6–11 and willing to take part in this study as respondents. Data collection was carried out from November 2022 to April 2023. There were 66 participants who met the criteria, and then an analysis was carried out using the Structural Equation Model (SEM) method, which was processed using Partial Least squares (PLS). Results: According to research findings, parents' points of view play an important role in deciding whether to vaccinate their child or not. Up to 58% of respondents said they support vaccinating their children, in this case with the COVID-19 vaccination. Conclussion: Parental attitudes of vaccination in children in this research is strongly influenced by parents' views, so the right approach is needed for parents for the successful implementation of vaccination in children. Other influential factors are spiritual context and generational influence from family regarding COVID-19.